Fine Tuning and Sterilization of Biodegradable Polymer for Medical Use: Case PLGA - Tähtinen, Taru (My University, 2026)
Biodegradable polymers have gained significant interest in medical applications due to their ability to degrade into biocompatible by-products. Poly (lactic-co-glycolic acid) (PLGA) represents a biodegradable copolymer with widely adjustable degradation behaviour and mechanical properties, offering the possibility to adjust the polymer properties to specific applications. This thesis examines the properties and fine-tuning of PLGA for medical use, focusing on the factors influencing its degradation rate, and evaluates sterilization methods for PLGA-based implants. Various factors influence the degradation behaviour of PLGA. In addition to copolymer composition, factors such as molecular weight, crystallinity, end-group functionalization, and monomer sequence affect the degradation rate of PLGA. Furthermore, biological factors, including enzymatic activity and inflammation, can alter the degradation rate and mechanism in vivo. Sterilization of PLGA-based implants presents a challenge due to the polymer’s sensitivity to heat, moisture and irradiation. Commonly applied methods for PLGA include gamma irradiation, electron beam irradiation and ethylene oxide. The selection of a sterilization method must consider the efficacy with the preservation of material properties and biocompatibility.

Biohajoavat polymeerit herättävät kiinnostusta lääketieteellisessä käytössä, sillä ne hajoavat bioyhteensopiviksi sivutuotteiksi. Poly(maito-ko-glykolihappo) (PLGA) on biohajoava kopolymeeri, jonka mekaanisia ominaisuuksia ja hajoamiskäyttäytymistä voidaan muokata laajasti. Tutkielmassa perehdytään PLGA:n ominaisuuksiin ja hienosäätöön, erityisesti sen hajoamisnopeuteen vaikuttaviin tekijöihin, sekä PLGA-pohjaisten implanttien sterilointimenetelmiin. PLGA:n hajoamiskäyttäytymiseen vaikuttavia tekijöitä on useita. Kopolymeerin monomeerisuhteen lisäksi molekyylimassa, kiderakenne, pääteryhmät ja monomeerien järjestys vaikuttavat PLGA:n hajoamisnopeuteen. Lisäksi biologiset tekijät, kuten entsymaattinen aktiivisuus ja paikallinen tulehdusreaktio, vaikuttavat hajoamiskäyttäytymiseen in vivo -olosuhteissa. Polymeerin herkkyys kuumuudelle, kosteudelle ja säteilylle vaikeuttaa PLGA-pohjaisten implanttien sterilointimenetelmän valintaa. Yleisimmin käytettyjä menetelmiä ovat gammasäteily, elektronisuihkusäteily ja etyleenioksidikaasu. Sopivan sterilointimenetelmän valinnassa tulee huomioida tehokkuus sekä polymeerin ominaisuuksien ja bioyhteensopivuuden säilyminen.
Keywords: biodegradable polymer; PLGA; degradation rate; sterilization; biohajoava polymeeri; hajoamisnopeus; sterilointi